ISOLASI DAN IDENTIFIKASI Pseudomonas DARI TANAH KEBUN BIOLOGI WAMENA DAN UJI AWAL SEBAGAI AGEN BIOKONTROL Fusarium - HJD Latupapua; N Nurhidayat (BERITA BIOLOGI, 2003)
Pseudomonas bacteria plays essential role in soil ecology such as decomposer and biological control. The bacteria were isolated on selective media and identified from five soil samples taken within area of Wamena Biological Gardens.There are six species Pseudomonas were indentified based on morphological characters and biochemical reaction.P. striata was found to be common in soil of the area.No pathogen Pseudomonas was indentified in all soil samples. Preliminary study on biological control for fungal pathogen Fusarium indicated that P. fluorescens, P. striata and P. cepacia have ability to inhibit Fusarium growth in vitro.